2008
DOI: 10.1002/eji.200838201
|View full text |Cite
|
Sign up to set email alerts
|

Resting B cells expand a CD4+CD25+Foxp3+ Treg population via TGF‐β3

Abstract: Regulatory T cells (Treg) play critical roles in maintaining tolerance and preventing autoimmunity. It is not fully clear how these cells are generated and maintained. Here, we show that resting B cells are able to expand Treg. This expansion requires TGF-b3 and signaling through the TCR and CD28. Upon activation, B cells express less TGF-b3, which reduces their capacity to expand Treg and which also results in increased Treg death. This may ensure that B cells can function as potent professional antigen prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 44 publications
(61 reference statements)
6
61
2
Order By: Relevance
“…GARP is known to bind to TGF-β1, TGF-β2, and TGF-β3 (45). There is evidence that resting B cells express higher levels of TGF-β3 than activated B cells and are able to expand Treg populations in a TGF-β3-dependent mechanism (83). However, GARP is not expressed by resting B cells, which leads us to believe that GARP primarily regulates the bioavailability of TGF-β1 and TGF-β2 isoforms, rather than TGF-β3, to exert its regulatory roles in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…GARP is known to bind to TGF-β1, TGF-β2, and TGF-β3 (45). There is evidence that resting B cells express higher levels of TGF-β3 than activated B cells and are able to expand Treg populations in a TGF-β3-dependent mechanism (83). However, GARP is not expressed by resting B cells, which leads us to believe that GARP primarily regulates the bioavailability of TGF-β1 and TGF-β2 isoforms, rather than TGF-β3, to exert its regulatory roles in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, in our TCR-HAxIg-HA mice, there is evidence of B-cell activation (A.S., unpublished results, 2003), and it has been shown that CD40L-activated human B cells can efficiently induce expansion of Tregs, 46 so it is not clear whether the activation state of the B cell plays a role. Cytokines, such as TGF-␤3, 47 TGF-␤1, 48 and IL-10, produced by follicular B cells 49 have also been reported to be involved in Treg induction by B cells. The precise mechanisms and molecules involved in our system are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of immunoregulation, TGF-␤3 has been shown to be more functionally potent than TGF-␤1 at inducing chemotaxis of human mast cells but is less effective at inhibiting proliferation of these cells (28). In addition, TGF-␤3 has also been reported to be secreted by resting B cells to promote the expansion of CD4 ϩ CD25 ϩ Foxp3 ϩ cells (57). However, combining resting B cells with purified CD4 ϩ CD25 Ϫ T cells did not result in de novo development of Tregs.…”
Section: Discussionmentioning
confidence: 99%